2001
DOI: 10.1164/ajrccm.164.9.2103086
|View full text |Cite
|
Sign up to set email alerts
|

The Nasal Passage of Subjects with Asthma Has a Decreased Ability to Warm and Humidify Inspired Air

Abstract: We previously showed that individuals with seasonal allergic rhinitis (SAR) had a reduced ability to condition air, which was improved by inflammation. We hypothesized that individuals with perennial allergic rhinitis (PAR) would condition air like SAR with inflammation. Because individuals with asthma usually have inflammation in the nose, we hypothesized that they would condition air like individuals with PAR. We performed a prospective, parallel study on 15 normal subjects, 15 subjects with SAR outside thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…Although used in research setting (43), no validation of these ratings in nasal pathology could be found in literature. Results have suggested that every nose is Ôindividually calibratedÕ, because of the interpatient variation, which makes interpatient comparisons less reliable but still significant (44,45).…”
Section: Subjective Methodsmentioning
confidence: 99%
“…Although used in research setting (43), no validation of these ratings in nasal pathology could be found in literature. Results have suggested that every nose is Ôindividually calibratedÕ, because of the interpatient variation, which makes interpatient comparisons less reliable but still significant (44,45).…”
Section: Subjective Methodsmentioning
confidence: 99%
“…Patients with chronic nasal disease suffer from decreased mucociliary clearance (2010) but no study exists showing its effect on the lower airways. The nasal passages of asthmatics have a decreased ability to warm and humidify inspired air (2011).…”
Section: Impact Of Nasal Function and Dysfunction On The Lower Airwaysmentioning
confidence: 99%
“…This is possible because of the highly vascularized mucosa, with a large amount of secretory glands. The importance of the conditioning capacity of the nose in patients with asthma and seasonal allergic rhinitis has been studied by Assanasen et al (18). They found that noses of subjects with asthma were less able to condition inhaled cold dry air compared with controls.…”
mentioning
confidence: 99%